R&D and Firm Performance in a Transition Economy - Dirk Czarnitzki; Kornelius Kraft (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
We estimate the effects of R&D on firms' credit ratings and on financial distress. The main purpose is the comparison of firms in Western Germany and Eastern Germany as a transitional economy. Innovative activity has a positive impact on firm value proxied by ratings in Western Germany, but a negative impact in Eastern Germany. We also consider future financial distress, and find that R&D in Eastern German firms leads to higher default risk, in contrast to Western Germany. There, R&D enhances future performance. This result is highly politically relevant, since the high level of subsidies present in Eastern Germany may be subject to misallocation.
Keywords: P27; O31; L33; O12; O38; 330; Transitional Economy; Credit Rating; Bankruptcy; Innovation; Policy; Industrielle Forschung; Unternehmensentwicklung; Kreditwürdigkeit; Konkurs; Innovationspolitik; Wirtschaftliche Anpassung; Vergleich; Alte Bundesländer; Deutschland; Deutschland